La Ética Como Garante De Confianza Y Fe Pública En Los Profesionales De Contaduría. (2021)
In the development of the article it can be observed what is the importance of ethics in the profession to strengthen trust and public faith, the ethics of the accountant as a guarantor of his actions when examining a test of economic facts, since they are examined the truthful evidence with a materiality or quality in its aspects, for the development of the activities of the economic entity and the expert behavior when facing the own standards. The importance of the accounting professional in giving public faith in Colombia is an investiture that the state grants him and its basis is the ethics of the human being; with which said trust is made because it complies with the ethical standards established by a public accountant when developing his profession. Ethics is a guarantor for the accountant due to his comprehensive training where each act as a human being reflects the importance and capacity of his values when determining the good and evil of an act, the own standards reflect the condition when strengthening trust or signing with public faith.